The South African National Defence Force, 1994–2009: A historical perspective - Wessels, Andre (Faculty of the Humanities, University of the Free State, 2010)
On 27 April the new South African National Defence Force (SANDF) was established, comprising of the old South African Defence Force, plus the defence forces of the TBVC countries, the military wings of the African National Congress and Pan-Africanist Congress, as well as certain KwaZulu-Natal Self-protection Forces. Proceeding from the assumption that any country undeniably needs a well-trained, well-equipped and disciplined defence force, it is the purpose of this article to provide a review of the history of the SANDF in the first 15 years of its existence (i.e. 1994-2009), and to critically analyse the developments in the SANDF during those years. The track record of the SANDF in the years 1994 to 2009 is evaluated, with special reference to integration, affirmative action and transformation in general. The SANDF’s order of battle in 2009 is compared with its 1994 order of battle; and the problems/challenges faced by the SANDF in the course of 15 years are discussed, including the controversial arms deal, the impact that HIV/AIDS has had on the SANDF, rationalisation, problems with regard to discipline, and the SANDF’s role in peace-keeping operations.
Keywords: South African National Defence Force; History; Transformation; Constitution of the Republic of South Africa, 1996